Adaptability and Performance in Nanostores: The Mediating Role of Quality Management Under Environmental Complexity - Ortega-Jimenez, Cesar H; Melgar-Martínez, Narciso A; Sabillon Palomeque, Dany N.; Tome, Jose R.; Acevedo-Amaya, Mario Roberto (LACCEI, 2025)
This study investigates the impact of adaptability on nanostore performance, emphasizing the mediating role of quality management practices and the moderating influence of environmental complexity. Focusing on nanostores, an understudied retail segment, the research aims to fill theoretical gaps and provide actionable insights for improving strategic decision-making and operational agility. The study highlights that adaptability, which encompasses flexibility and responsiveness as key components, is crucial for performance improvement when integrated with robust quality management practices. Using advanced quantitative methods, including multivariate regression analysis, survey data from 143 nanostore owners and managers were analyzed. The results show that adaptability positively affects performance, with quality management practices mediating this relationship. Environmental complexity, while influencing the adaptability-performance link, presents challenges in highly volatile markets. Future research should address the small sample size and the use of cross-sectional data, considering longitudinal designs that allow for a deeper understanding of the dynamics over time. It would also be valuable to investigate regional variations to enhance the generalizability of the findings across different economic contexts. Additionally, exploring additional mediating factors, such as technology adoption, could provide further insights into the mechanisms influencing the observed outcomes. Nanostore operators are advised to adopt adaptability-driven strategies and integrate structured quality management practices to enhance performance. Policymakers can use these findings to support small retailers, especially in volatile market environments, fostering economic resilience. This research offers novel insights into the role of adaptability in nanostores and contributes to both academic literature and retail practice.